2015
DOI: 10.17265/2159-5275/2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Blade Mistuning in a Low Pressure Turbine Rotor Resulting from Manufacturing Tolerances and Differences in Blade Mounting

Abstract: For a serious prediction of vibration characteristics of any structure, a detailed knowledge of the modal characteristic is essential. This is especially important for bladed turbine rotors. Mistuning of the blading of a turbine rotor can appear due to manufacturing tolerances or because of the blading process itself due to unequal mounting of the blades into the disk. This paper investigates the mistuning of the individual blades of a low pressure turbine with respect to the effects mentioned above. Two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Dynamic stresses are influenced by the magnitude and source of excitation, the damping of the blade, and the degree of geometrical mistuning of the turbomachinery blade [18]. Dimensional imperfections and deviations are due to tolerances and manufacturing process, material inhomogeneity, and wear in service [19]. These deviations lead to mistuning and can increase the forced response vibration amplitude, increasing the HCF; this is commonly called mistuning.…”
Section: High Cycle Fatigue (Hcf)mentioning
confidence: 99%
“…Dynamic stresses are influenced by the magnitude and source of excitation, the damping of the blade, and the degree of geometrical mistuning of the turbomachinery blade [18]. Dimensional imperfections and deviations are due to tolerances and manufacturing process, material inhomogeneity, and wear in service [19]. These deviations lead to mistuning and can increase the forced response vibration amplitude, increasing the HCF; this is commonly called mistuning.…”
Section: High Cycle Fatigue (Hcf)mentioning
confidence: 99%
“…The intrinsic ductile nature of ASTM 304 stainless steel facilitates a nuanced plastic deformation at the root contact, thereby enhancing the distribution of loads. This property holds significant implications for preventing failures and cracks, as underscored by findings reported in the study by Schönleitner et al [5]. Consequently, the selection of ASTM 304 stainless steel as the focal material for this investigation is rooted in its tailored characteristics to address the critical challenges associated with steam turbine blade performance.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Rao and Vyas [4] found that dynamic stresses are influenced by the magnitude and source of the excitation, blade damping and the degree of the turbomachinery blade geometrical mistuning. As highlighted by Schönleitner et al [5], dimensional imperfections and deviations are due to the tolerances and manufacturing process, material inhomogeneity and in-service wear. These deviations lead to structural mistuning and can increase the forced response vibration amplitude which increases HCF.…”
Section: Introductionmentioning
confidence: 99%
“…The 304 stainless steel is favored for its wide application, especially in blades subject to significant centrifugal and bending loads within steam turbines. Its remarkable ductility allows for nuanced plastic deformation at the root contact, preventing failures and cracks, as seen in Schönleitner et al (2015). This material is chosen for its tailored characteristics that address steam turbine blade challenges, and this paper thoroughly examines the behavior of the material in the context of steam turbine applications.…”
Section: Introductionmentioning
confidence: 99%